Activin A stimulates migration of the fallopian tube epithelium, an origin of high-grade serous ovarian cancer, through non-canonical signaling. (10th April 2017) - Dean, Matthew; Davis, David A.; Burdette, Joanna E.
Abstract: Factors that stimulate the migration of fallopian tube epithelial (FTE)-derived high-grade serous ovarian cancer (HGSOC) to the ovary are poorly elucidated. This study characterized the effect of the ovarian hormone, activin A, on normal FTE and HGSOC. Activin A and TGFβ1 induced an epithelial-to-mesenchymal transition in murine oviductal epithelial (MOE) cells, but only activin A increased migration. The migratory effect of activin A was independent of Smad2/3 and required phospho-AKT, phospho-ERK, and Rac1. Exogenous activin A stimulated migration of the HGSOC cell line OVCAR3 through a similar mechanism. Activin A signaling inhibitors, SB431542 and follistatin, reduced migration in OVCAR4 cells, which expressed activin A subunits (encoded by INHBA). Murine superovulation increased phospho-Smad2/3 immunostaining in the FTE. In Oncomine, transcripts for the activin A receptors ( ACVR1B and ACVR2A ) were higher in serous tumors relative to the normal ovary, while inhibitors of activin A signaling (INHA and TGFB3 ) were lower. High expression of both INHBA and ACVR2A, but not TGFβ receptors or co-receptors, was associated with shorter disease-free survival in serous cancer patients. These results suggest activin A stimulates migration of FTE-derived tumors to the ovary. Highlights: Activin A stimulates migration of normal fallopian tube epithelial cells. The migratory effect of activin A is mediated by non-canonical pathways. Activin A stimulates migration of high grade serous cells. INHBA and ACVR2 are associated with shorter disease-free survival.